(untitled) (Global Journal of Management and Business Research, 2017)
Along with the opportunities for economic development from the opening policy, Vietnam’s economy is facing many risks, including reduction in competitiveness capacity and the annexation of foreign enterprises that are the phenomenons predicted in the short and long term. In the context of deep integration, Vietnam has participated in many free-trade agreements with a strong commitment on opening the retail market and elimination of tariff barriers and non-tariff for goods, the retail sector of Vietnam is facing many significant challenges. Particularly in the retail sector with great potential, attraction, Vietnam’s retail market is strongly attracting investment from the foreign retailers. In the past time, there has been a change of owners of many supermarkets and the investment and expansion of distribution network of foreign retailers that have made the domestic enterprises at risk of losing markets. With this competition, the enterprises’ associating and sharing interests to support others’ development is necessary. The question that if the State will have any policies to support the dosmetic retailers is interested by many people.